Mannan-Binding Lectin Regulates the Th17/Treg Axis Through JAK/STAT and TGF-β/SMAD Signaling Against Candida albicans Infection - Wang F; Yang Y; Li Z; Wang Y; Zhang Z; Zhang W; Mu Y; Yang J; Yu L; Wang M (Dove Medical Press, 2022)
Fanping Wang,1,2 Yonghui Yang,1,3 Zhixin Li,1,2 Yan Wang,1,4 Zhenchao Zhang,2,5 Wei Zhang,2,5 Yonghui Mu,2,5 Jingwen Yang,1,2 Lili Yu,2,5 Mingyong Wang1,2 1Henan Key Laboratory of Immunology and Targeted Drugs, School of Laboratory Medicine, Xinxiang Medical University, Xinxiang, Henan, 453003, People's Republic of China; 2Xinxiang Key Laboratory of Immunoregulation and Molecular Diagnostics, Xinxiang, 453003, People's Republic of China; 3Henan Center for Disease Control and Prevention, Zhengzhou, Henan, 450000, People's Republic of China; 4Department of Laboratory Medicine, Luoyang Oriental Hospital, Luoyang, Henan, 471000, People's Republic of China; 5School of Basic Medical Sciences, Xinxiang Medical University, Xinxiang, Henan, 453003, People's Republic of ChinaCorrespondence: Mingyong Wang; Lili Yu, Email wmy118@126.com; merrys222@126.comBackground: Mannan-binding lectin (MBL) is a key molecule in innate immunity and activates the lectin complement pathway, which plays an important role in resisting Candida albicans (C. albicans) infection. However, the underlying mechanism of this resistance to infection remains unclear.Methods: In this study, we investigated how MBL regulates the differentiation of CD4+ T cells into T helper type 17 (Th17) and T regulatory (Treg) cells against C. albicans in mice, as well as the underlying mechanisms. We generated MBL double-knockout (KO) mice and infected them with C. albicans by intraperitoneal injection.Results: Compared with that in wild-type (WT) mice, the percentage of Th17 cells increased in MBL-null mice, whereas Treg cells decreased, indicating that MBL might regulate the Th17/Treg balance. In addition, in MBL-null mice, the expression levels of interleukin (IL)-17A, IL-21, and the master transcription factor of Th17 cells, RORγt, significantly increased. Conversely, IL-10, IL-2, and the Treg-specific transcription factor, Foxp3, decreased. Moreover, we found that the levels of TGF-β and IL-6 upregulated in MBL-null mice. Mechanistically, we found that MBL regulated the TGF-β/SMAD pathway through the inhibition of p-SMAD2 and promotion of p-SMAD3, and mediated the JAK/STAT pathway through the inhibition of p-JAK2 and p-STAT3 and promotion of p-JAK3 and p-STAT5. MBL double-KO mice showed a more severe inflammatory response and significantly lower survival rates with C. albicans infection.Conclusion: These results suggest that MBL regulates the Th17/Treg cell balance to inhibit inflammatory responses, possibly via IL-6- and TGF-β-mediated JAK/STAT and TGF-β/SMAD signaling, and play an important role in anti-C. albicans infection.Keywords: mannan-binding lectin, Th17/Treg axis, JAK/STAT, TGF-β/SMAD, Candida albicans